Exosome-driven liquid biopsy for breast cancer: Recent advances in isolation, biomarker identification and detection - Junjie Zhao; Lizhou Xu; Dongjie Yang; Huijing Tang; Yalin Chen; Xunzhi Zhang; Yunsheng Xu; Rongying Ou; Danyang Li (Extracellular Vesicle)
Liquid biopsy with minimally invasive emerges as a powerful tool for early screening of breast cancer (BrCa). BrCa derived exosomes which enrich with biological information from their parent cells play essential roles in the evolution and metastasis of BrCa, providing a real-time snapshot of the tumor. This review summaries the recent advances of exosomes studies in liquid biopsy, particularly for BrCa. A number of isolation methods for exosomes are compared in detail. Different exosome biomarkers for detection of BrCa are discussed. Novel approaches for the detection of exosomes towards clinical diagnosis of BrCa are highlighted at the end. We believe the innovations in exosome research will lead to new breakthroughs in the early screening and diagnosis of BrCa.